From the board of the bank: sorne experiences and reflections (1997)
This article presents some interesting and polemical reflections about the Central Bank, the degree of credibility of its policies, the setting of goals in matters of monetary and exchange rate policy, the use of available instruments, and the trade-off between inflation and unemployment. For the author, autonomy is a necessary but not sufficient condition for achieving a lower rate of inflation. The struggle against inflation requires a large degree of social support, coordination between all the economic institutions of the State, and the responsibility of private institutions. The problem of dynamic inconsistency between credibility and results would be resolved when there is recogni tion of the superiori ty of an adjustable rule, in which credibility would be the result of a dynamic process of mutual teaching and learning between economic agents and the Central Bank, and in which economic policy instruments achieve a greater stability beca use a short term vision is transcended.